The concentration effect of kulim leaf (scorodocarpus borneensis) extract on Streptococcus mutans ATCC 25175 bacterial hydrophobicity and adhesion - Utami, Trianna Wahyu; Hapsari, Adhaninggar Ratna; Hanalda, Dhe Rifdania; Nur, Asikin; Yulianto, Heribertus Dedy Kusuma; Purwanti, Nunuk (Majalah Kedokteran Gigi Indonesia, 2022)
With the ability to reduce hydrophobicity and inhibit the adhesion of S. mutans ATCC 25175 bacteria, Kulim leaf extract can be used as an alternative to chlorhexidine mouthwash in caries prevention. The objectives of this study are to determine the effect of Kulim leaf extract on hydrophobicity and adherence of the cariogenic bacteria S. mutans ATCC 25175. The test groups were divided into negative control (DMSO 2%), the treatment group (Kulim leaf extractconcentrations of 1.25%, 2.5%, 5%), and positive control (0.1% chlorhexidine). All of groups were received three replicated tests for hydrophobicity and adherence inhibition of S. mutans ATCC 25175 bacteria. The hydrophobicity test was conducted by providing 3 ml of bacterial suspension of S. mutans ATCC 25175 which had been adjusted to the McFarland 0.5 standard for each group. Furthermore, each test group was vortexed for one minute and left to stand for 15 minutes. Each treatment was tested with a wavelength spectrophotometer of 550 nm before and after the provision of 200 µl of n-hexadecane. The absorbance value on the spectrophotometer was then included in the hydrophobicity formula to determine the hydrophobicity percentage of S. mutans ATCC 25175 against n-hexadecane. To test the bacterial adhesion, the 96 wells microplate was inserted with the kulim leaf extract of each concentration,BHI-B, bacteria according to the McFarland 0.5 standard, and for the positive control and negative control. Afterwards, they were incubated at 37 °C for 24 hours before they were rinsed with distilled water, and stained with 0.1% crystal violet. Then, an optical density reading was performed using a microplate reader with a wavelength of 540 nm. The absorbance value was then included in the formula for percentage of bacterial adhesion inhibition. Post-Hoc LSD testshowed a significant difference in mean difference between the negative control group and the other treatment groups (p<0.05). In addition, it was revealed that there was no significant mean difference between treatment groups, and there was no significant difference between positive control and treatment groups of 2.5% and 5% in the hydrophobicity test. However, there was a significant difference between the positive control and the treatment group of 1.25% in the hydrophobicity test and the treatment group of 1.25%, 2.5%, and 5% in the adherence test. This study concluded that Kulim leaf extract concentration affected hydrophobicity and attachment of S. mutans ATCC 25175 with an effective concentration of 2.5%.